Benthic effects of offshore renewables: identification of knowledge gaps and urgently needed research. (1st March 2019) - Dannheim, Jennifer; Bergström, Lena; Birchenough, Silvana N R; Brzana, Radosław; Boon, Arjen R; Coolen, Joop W P; Dauvin, Jean-Claude; De Mesel, Ilse; Derweduwen, Jozefien; Gill, Andrew B; Hutchison, Zoë L; Jackson, Angus C; et al.
Abstract: As the EU's commitment to renewable energy is projected to grow to 20% of energy generation by 2020, the use of marine renewable energy from wind, wave and tidal resources is increasing. This literature review (233 studies) (i) summarizes knowledge on how marine renewable energy devices affect benthic environments, (ii) explains how these effects could alter ecosystem processes that support major ecosystem services and (iii) provides an approach to determine urgent research needs. Conceptual diagrams were set up to structure hypothesized cause-effect relationships (i.e. paths). Paths were scored for (i) temporal and spatial scale of the effect, (ii) benthic sensitivity to these effects, (iii) the effect consistency and iv) scoring confidence, and consecutively ranked. This approach identified prominent knowledge gaps and research needs about (a) hydrodynamic changes possibly resulting in altered primary production with potential consequences for filter feeders, (b) the introduction and range expansion of non-native species (through stepping stone effects) and, (c) noise and vibration effects on benthic organisms. Our results further provide evidence that benthic sensitivity to offshore renewable effects is higher than previously indicated. Knowledge on changes of ecological functioning through cascading effects is limited and requires distinct hypothesis-driven research combined with integrative ecological modelling.